Effect of fracture on production characteristics and oil distribution during CO2 huff-n-puff under tight and low-permeability conditions. (15th June 2019) - Bai, Hao; Zhang, Qiliang; Li, Zhaomin; Li, Binfei; Zhu, Di; Zhang, Liaoyuan; Lv, Guangzhong
Abstract: CO2 injection is an effective technique to enhance the oil recovery of tight or low-permeability reservoirs, which also achieves resource utilization and geological storage of CO2. While the fractures in the formation have remarkable effect on the performance of CO2 injection. In this study, CO2 huff-n-puff experiments were carried out with fractured cores, and the NMR was used to investigate the oil distribution. The effects of fractures on CO2 huff-n-puff and remaining oil distribution at different permeability levels were evaluated. The experimental results show that fracture can significantly increase the CO2 sweep volume of the core, and the oil recovery rate is sharply improved in the initial and middle stages during CO2 huff-n-puff. Besides, the remaining oil saturation significantly decreases near the fracture. The final oil recovery of the fractured cores enhanced by ∼14% compared with that of fracture-free cores. The permeability of matrix remarkably affects the CO2 huff-n-puff of fracture-free cores, whereas its effect on fractured cores is relatively small, fractures can reduce the effect of permeability on recovery. The crude oil is mainly produced from the macropores and the remaining oil in the cores is mainly distributed in the small and medium pores. Moreover, an increase in the number of cycles can improve the cumulative oil recovery, but as the number of cycles increases, the production of new crude oil decreases. This study provides a reference to evaluate the oil production characteristics of fractured reservoirs and improve the production performance.